Characterization of partial discharges in slots and by vibration in stators of hydrogenators - Nuñez Mata, Oscar (2021)
The reliability and availability of hydro generators is highly dependent on the condition of the stator insulation, which is exposed to a combination of thermal, electrical, environmental and mechanical stresses. An unscheduled interruption of a generator in operation could jeopardize system stability, as well as cause economic losses, so it is necessary to have condition monitoring techniques, such as on-line partial discharge measurement. A partial discharge is defined as a localized electrical discharge, which only partially joins the insulation between the conductors, accompanied by movement of charges, acoustic emission, radiation and chemical reaction, among other effects. On-line partial discharge measurement is one of the most used techniques to follow the evolution of large hydro generators. This article proposes a novel methodology to detect the failure mechanisms of partial discharges: i) in slot; and, ii) by sparks produced by vibration, showing one example using a generator in service. The methodology is based on on-line partial discharge measurement for different active power levels. The above allows finding thermal and mechanical dependencies, which are able to locate and characterize the failure mechanism. Subsequently, a series of possible root causes of each are established, and recommendations for repair. The results obtained in the tests carried out show that on-line partial discharge measurement is effective when it comes to early detection of sudden failures, and has been successfully applied in the hydro generator evaluated.